Mechanisms of cnidocyte development in the moon jellyfish Aurelia. Issue 2 (8th January 2019) - Gold, David A.; Lau, Clive Long Fung; Fuong, Holly; Kao, Gregory; Hartenstein, Volker; Jacobs, David K.
Abstract : Stinging cells called cnidocytes are a defining trait of the cnidarians (sea anemones, corals, jellyfish, and their relatives). In hydrozoan cnidarians such as Hydra, cnidocytes develop from interstitial stem cells set aside in the ectoderm. It is less clear how cnidocytes develop outside the Hydrozoa, as other cnidarians appear to lack interstitial stem cells. We addressed this question by studying cnidogenesis in the moon jellyfish (Aurelia) through the visualization of minicollagen—a protein associated with cnidocyte development—as well as transmission electron microscopy. We discovered that developing cnidoblasts are rare or absent in feeding structures rich in mature cnidocytes, such as tentacles and lappets. Using transmission electron microscopy, we determined that the progenitors of cnidocytes have traits consistent with epitheliomuscular cells. Our data suggests a dynamic where cnidocytes develop at high concentrations in the epithelium of more proximal regions, and subsequently migrate to more distal regions where they exhibit high usage and turnover. Similar to some anthozoans, cnidocytes in Aurelia do not appear to be generated by interstitial stem cells; instead, epitheliomuscular cells appear to be the progenitor cell type. This observation polarizes the evolution of cnidogenesis, and raises the question of how interstitial stem cells came to regulate cnidogenesis in hydrozoans.